Household search and the aggregate labor market - Jochen Mankart; Rigas Oikonomou (Deutsche Bundesbank, 2015)
We develop a theoretical model with labor market frictions, incomplete financial markets and with households which have two members. Households face unemployment risks but their members adjust their labor supplies to insure against unemployment. We use the model to explain the cyclical properties of aggregate employment and participation. As in the US data, the model predicts that the participation rate (the fraction of individuals that want jobs) is not strongly correlated with aggregate economic activity. This property is in sharp contrast to the strongly procyclical participation predicted by both neoclassical models and models with search frictions, when we assume bachelor households or households with infinitely many members (complete markets). In the two member household model and in the data, primary earners are always in the labor force, secondary earners have a mildly countercyclical participation rate and a mildly procyclical employment rate. Their behavior insures the household against unemployment risks.
Keywords: E24; E25; E32; J10; J64; 330; Heterogeneous Agents; Family Self Insurance; Labor Market Search; Aggregate Fluctuations